Flash vaporization of propane in an optically accessible, directly injected engine. (February 2021) - Lacey, Joshua; Aditiya, Harjon; Poursadegh, Farzad; Brear, Michael; Gordon, Robert; Lakey, Charles; Butcher, Brendan; Ryan, Steve
This article presents an experimental and thermodynamic analysis of the direct injection of propane in an optically accessible variant of a downsized production engine. Propane is used as a surrogate for liquefied petroleum gas and is tested at several fuel rail conditions. Imaging of the sprays' structure is conducted using planar laser Mie scattering. A number of seemingly counter-intuitive trends relating to rail pressure and temperature are observed from the experiments, and thermodynamic investigation is conducted to explain these trends. It is concluded that flash-boiling induced vaporization external to the injector nozzle is largely responsible for the observed behavior, and a new quantity is proposed to describe the severity of this phenomenon.